316 Fit of N95 filtering facepiece respirators influenced by gender, design of facepiece, and activity engaged in use. (11th October 2013) - Lin, Y C; Chen, C-P
Abstract : Objectives: The N95 filtering facepiece respirators are often used as the last line of defense protecting the workers against threats of airborne particulate contaminants, and its leakage around the faceseal could result in a direct exposure to the unfiltered air. This study investigated the fit of N95 respirators among young Taiwanese under the influences of gender, facepiece design, and activity engaged when the respirators were used. Methods: In the study, all participants (60 males and 60 females) were first characterised for 19 facial dimensions frequently applied in fit-test panel design using anthropometric equipments. The participants were then qualitatively fit-tested with N95 masks of three distinct facepiece designs (cup, flat fold, and liner with exhalation valve). During the fit-test, the participants were required to perform a series of seven exercises. The results were compared using Principle Component Analysis to identify key facial dimensions influencing the respirator fit as well as their distributions. Results: Only 27% of the participants passed all seven exercises without a leakage detected, with the proportion in males significantly higher than that of females. The percentage of participants failing all exercises was the greatest with the liner model and the least with the flat-fold model. When the flat-fold and cup models were tested, deep breathing and talking resulted in higher rate of leakage than the others activities. The facial dimensions identified as being significant to respirator fit included face width, interpupillary distance, nose breadth, face length, nose protrusion, and subnasale-sellion length. Conclusions: The facial dimensions significant to respirator fit among Taiwanese suggested a need for a Taiwanese-based respirator fit-test panel. The users should include the flexibility of facepiece and the activity engaged when using the respirator as factors to consider when selecting a respirator so to reduce potential exposure due to inappropriate fit.